STYLE AND VISUAL DISCOURSE IN IRAQI PAINTING-MAHOOD AHMED AS A MODEL - Mona Haider Ali Hassan (Scholars Digest Publishing, 2024)
Beyond the methods, vocabulary, and visual discourse of Mahood Ahmed's works, there has been a significant change in how artistic elements are creatively employed and the artistic topics presented. This has been achieved through the use of beautiful shapes, styles, formations, and blocks as well as the embodiment of the essential ideas of the subject matter, where the appropriate atmosphere is created in addition to the process of creating a natural illusion of time and place, the creation of a dramatic sequence through events and visual scenes, and the intervention of artwork elements to visually add their charm and artistic, aesthetic, and rhythmic touches, thereby leaving the viewer with a lasting sensory memory. For the first chapter, we talked about the research problem, the importance of research, the objectives of the research, the limits of the research, and the definition and renewal of terms, and we dealt in the second chapter with two sections, the first is artistic formation in drawing, the second topic is narration and modern artistic methods of the artist Mahood Ahmed and indicators of the theoretical framework, and the third chapter dealt with the procedures for research and analysis of samples, while the fourth chapter is the results, conclusions, recommendations and proposals.
Keywords: Style – visual discourse – drawing.